Social Studies in the Frame of 21st Century Education - Gusmira Wita; Irhas Fansuri Mursal (Proceeding International Conference on Malay Identity, 2021)
Abstract: Learning social studies has an important role for students because social studies is related to various aspects of human life which involve behavior in meeting aspects of life's needs and social studies is related to how humans use their efforts to meet their needs. In essence, what is studied in social studies is how to study, examine, study the system of human life in society. The needs of the 21st century demand that the learning model applied in the social studies learning process is able to develop students' high-level thinking skills which in Bloom's Taxonomy include the ability to analyze (C4), evaluate (C5) and create (C6). Thus the learning process produces excellent human resources, capable of critical thinking and readiness to face rapid changes in global society. Keywords: social studies, 21st century, higher order thinking.